Evaluation of predictor factors of psychological distress in women with unexplained infertility - Ingrid Noël; Sylvie Dodin; Stéphanie Dufour; Marie-Ève Bergeron; Jessica Lefebvre; Sarah Maheux-Lacroix (SAGE Publishing, 2022)
Objective: The objective of this study was to establish the frequency of anxiety and depressive symptoms among women diagnosed with unexplained infertility and to identify risk factors. Methods: We conducted a descriptive cross-sectional study. Forty-two women from the CHU de Quebec fertility clinic were recruited. Women completed the 'Hospital Anxiety and Depression Scale' (HADS) self-administered questionnaire, used to estimate prevalence of anxiety and depressive symptoms (score ≥ 8). Results: Overall, 55% ( n  = 23) of participants were identified with anxiety or depressive symptoms according to the HADS questionnaire. Anxiety symptoms were more frequent (55%) compared with depressive symptoms (10%). According to a logistic regression model, being under 35 years old [odds ratio (OR) = 16.6, confidence interval (CI): 1.9-25.0], never had a previous spontaneous abortion (OR = 5.6, CI: 1.1-43.5) and never sought fertility treatment (OR = 5.5, CI: 1.1-45.4) were associated with a higher risk of anxiety and depressive symptoms. Conclusion: Anxiety and depressive symptoms are common among women with unexplained infertility, and strategies should be developed to better support and treat this high-risk population.